Age-dependent cardiovascular adverse event reporting with pathway-directed anticancer therapies in children and adults: A VigiBase disproportionality analysis - Labombarda, Fabien; Bodet, Damien; Rouger, Jérémie; Guerin, C; Sassier, Marion; Chrétien, Basile; Alexandre, Joachim; Dolladille, Charles (Pediatric Blood & Cancer, 2026)
BACKGROUND: Cardiac monitoring in children receiving pathway-directed anticancer therapies is largely extrapolated from adult cardio-oncology practice. Developmental differences in cardiovascular physiology raise the possibility that treatment-related cardiovascular toxicity may not present similarly across ages. Whether the pattern of cardiovascular adverse events associated with these therapies differs between children and adults remains uncertain. METHODS: We conducted a retrospective pharmacovigilance study using VigiBase, the World Health Organization global database of individual case safety reports (March 2025 extract). Reports involving pathway-directed anticancer therapies, including kinase and proteasome inhibitors, were classified as minors (<18 years) or adults (≥18 years). Cardiovascular adverse events were identified using predefined terms. Within-drug disproportionality analyses adjusted for sex were performed with age-stratified and indication-matched sensitivity analyses. RESULTS: A total of 5097 pediatric and 273,833 adult reports were analyzed. Cardiovascular reporting patterns differed markedly between age groups. Vascular and ischemic complications and supraventricular arrhythmias were rarely reported in children. In contrast, pediatric reports were predominantly characterized by myocardial dysfunction, including decreased ejection fraction and heart failure, with occasional repolarization abnormalities. Findings were consistent across pediatric age groups and after adjustment for concomitant cardiotoxic therapies, including anthracyclines. Limited drug-event associations were observed for selected agents, mainly involving myocardial dysfunction. CONCLUSIONS: These therapies showed an age-dependent pattern of cardiovascular adverse event reporting, predominantly myocardial in children and vascular-ischemic in adults. Pediatric cardiac surveillance should therefore prioritize assessment of myocardial function during treatment rather than directly mirroring adult monitoring strategies. Prospective studies with standardized cardiac evaluation are needed to inform age-adapted monitoring.